Perception of oncology practitioners towards off‐label use of anticancer medicines in Singapore. Issue 2 (20th April 2017) - Saiyed, Mohd Masnoon; Ong, Pei Shi; Chew, Lita
Abstract: Objectives: Prescribing drugs outside regulatory recommendation is known as off‐label use. Studies have reported widespread off‐label drug use in oncology practice. But the clinical, economic and humanistic outcomes for such practice are often uncertain. Hence, it is important to gather oncology practitioners' perspective for the creation of clinical practice framework and policies. The aim of the study was to evaluate perception of oncology practitioners on off‐label use in cancer therapy. Methods: This study employed a cross‐sectional design implemented in the form of the self‐administered questionnaire at National Cancer Centre Singapore where more than 50% cancer patients of the country are treated. Key findings: Eighty‐one practitioners involving nurses (38%), medical oncologist (37%) and pharmacists (25%) were surveyed. The majority of practitioners (57%) agreed off‐label use as indispensable practice in cancer therapy. Main reasons cited include advanced cancers where standard lines of treatment are exhausted (58%), lack of alternative approved drug (43%) and rare tumours (47%). Compared with other practitioners, medical oncologists viewed Phase 2 (73% versus 31%, P = 0.001) and conference abstracts (56% versus 23%, P = 0.003) as reasonable evidence for off‐label use. Major concerns included lack of efficacy (58%), patient understanding (47%), uncertain safety (43%) and out‐of‐pocket cost (41%) associated with off‐label use. Most viewed need for obtaining informed consent (86%) and institutional guidance (75%) as important elements in practice framework. Conclusion: The study provides insights about off‐label drug use practice and establishes the need for robust clinical guidance and educational strategies for oncology practitioners.